Corrosion atlas : a collection of illustrated case histories - During, Evert D. D., 1933- (Elsevier, 2018)
Includes 679 case histories divided over 135 materials in 13 material groups, 25 systems (installations) and 44 different phenomena. It is an essential reference work on the design, fabrication, operation and maintenance of the extremely varied and often very complicated systems and machinery used in today's technology. Case histories, with cross-references and indexes, make this book a critical resource in the solution of many corrosion problems. In addition, it brings team members closer by presenting a common language for all parties. Finally, the book serves as an important educational aid for self-study.